A dual-site controlled fluorescent sensor for the facile and fast detection of H2O in D2O by two turn-on emission signals. Issue 8 (3rd January 2020) - Dong, Baoli; Lu, Yaru; Song, Wenhui; Kong, Xiuqi; Sun, Yaru; Lin, Weiying
Abstract : A dual-site controlled fluorescent sensor based on FRET mechanism was constructed for the facile and fast detection of H2 O content in D2 O. Abstract : Currently, fluorescent sensors for the detection of H2 O in D2 O are still quite rare. Herein, we present a dual-site controlled fluorescent sensor (CF-D2 O ) for the detection of H2 O in D2 O. As the H2 O content in D2 O decreases (namely, the purity of D2 O increases), sensor CF-D2 O provides two turn-on fluorescence signals. The response mechanism of sensor CF-D2 O to H2 O is based on the deprotonation of the two hydroxyl groups, as well as the FRET process between coumarin and xanthene units.